The Implication of Property Classification on Contract Validity and Tasharruf Rights: A Comparative Analysis of Fiqh Schools - Susandi, Adi; Fattah, Abdul; Jubaedah , Dedah; Setiawan, Iwan (Zona Law And Public Administration Indonesia, 2025)
Property (al-māl) occupies a central position in Islamic law as part of Maqāṣid al-Syarī‘ah. However, there is a fundamental divergence among Fiqh schools regarding its ontological definition. The Hanafi school emphasizes a materialistic approach requiring physical existence and storability while the Majority (Jumhur) scholars (Maliki, Shafi'i, and Hanbali) adopt a value-based functional approach. This study aims to analyze these comparative views and their implications for contract validity and disposal rights (ḥaq taṣarruf), particularly within the context of the digital economy. Using a qualitative library research method with a juridical-normative approach, this study finds that the Jumhur’s definition is more adaptive to modern intangible assets such as cryptocurrencies and NFTs. Conversely, the Hanafi distinction between invalid (fāsid) and void (bāṭil) contracts offers legal stability in transactions. The study concludes that a methodological synthesis between Hanafi’s legal rationality and the Jumhur’s value-orientation is necessary to construct a contemporary Fiqh Muamalah that is responsive to technological disruption while maintaining Sharia compliance